Changes in inflammatory factors in the Brown Norway rat model of food allergy - Qingling Zhu; Junli Wang; Jingqiu Ma; Xiaoyang Sheng; Feng Li (BMC Immunology, 2021)
Abstract Background The role of serum S100A8/A9 in intestinal inflammation has been confirmed, and its role in food allergy is currently being investigated. Objective To explore the levels of S100A8/A9 and inflammatory factors, including Toll-like receptors 4 (TLR4), Nuclear transcription factors (NF-κB) and Tumor necrosis factor α (TNF-α), in mild food allergies. Methods Eighty 3-week-old male Brown Norway rats were used. Forty rats were randomly assigned to the ovalbumin-sensitized experimental group, while 40 rats were assigned to the normal saline sham-sensitized control group. Body weight and length and the levels of serum ovalbumin-specific IgE (OVA-IgE), histamine, Th1-associated and Th2-associated factors, S100A8/A9 and inflammation-associated cytokines were compared. Results Through the evaluation of OVA-IgE level and Th1/Th2 balance in the experimental group, a successful IgE-mediated food allergy model was constructed. Compared with the control group, the experimental group had higher serum S100A8/A9 levels on days 21, 28, 35 and 42 (all P < 0.05); higher TLR4 levels on days 28, 35 and 42 (all P < 0.05); higher TNF-α levels on days 28, 35 and 42 (all P < 0.05); higher NF-κB levels on days 35 and 42 (all P < 0.05); and higher IL-1β and IL-6 levels on days 7 to 42 (all P < 0.05). Moreover, positive correlations were found between the serum levels of S100A8/A9 and inflammation-associated cytokines [TNF-α: r = 0.378, P = 0.039; IL-1β: r = 0.679, P = 0.000; IL-6: r = 0.590, P = 0.001]. Conclusion S100A8/A9 and inflammatory-related factors, including TLR4, NF-κB, TNF-α, IL-6 and IL-1β, is closely related to food allergies. Moreover, immune and inflammatory factors interact with each other in food allergies, which may provide insight into food allergy causes and treatments.